Quality of Life Among Male Patients Undergoing Hemodialysis: A KDQOL-SF-Based Study - Iriane, Vincentia Maria; Setyawan, Yuswanto (Universitas Ibn Khaldun Bogor, 2025)
This study aims to explore the quality of life of male patients undergoing hemodialysis using the KDQOL-SF (Kidney Disease Quality of Life Short Form) instrument. Hemodialysis is a crucial therapy for patients with chronic kidney disease (CKD), but it has a significant impact on the patients' quality of life, both physically and psychosocially. The population selected in this study consists of CKD patients currently undergoing hemodialysis in Malang. The sample will include 100 patients aged 50-70 years in Malang. The collected data will then be statistically analyzed using Chi-square and Spearman's rank correlation test. Based on the Spearman correlation, the quality of life of chronic kidney patients increased by 59% and was shown to have a significant effect. Men generally tend to be less emotionally expressive and are more likely to internalize their burdens. If they lack a supportive psychosocial environment, feelings of loneliness and isolation increase, worsening depressive symptoms. Kidney disease causes an accumulation of toxins (uremia), which is known to affect brain function and mood. Hormonal imbalances due to kidney dysfunction may also lead to decreased levels of serotonin and testosterone, contributing to depression and reduced energy. It is recommended to conduct longitudinal studies to observe the psychological changes in male patients from the start of therapy to the following years. It is also important to explore gender-sensitive approaches, as men and women have different ways of coping with chronic illness. Focusing on masculinity, social roles, and self-identity could be a relevant research theme.